Attack of the jack-o'-lanterns - Stine, R. L. (New York, NY : Scholastic Inc., 2018)
Drew and her friend Walker, desperate to get revenge against Tabby and Lee for a nasty Halloween joke, come up with a plan designed to scare the wits out of the snobby duo.
3.8
5-8
5-8
Keywords: Halloween -- Juvenile fiction; Halloween -- Fiction; Halloween -- Fiction; Horror fiction